Sugar use in relation to shoot induction by sorbitol and cytokinin in apple - Karhu, Saila T. (us, 1997)
Microshoots of 'McIntosh' apple (Malus domestica Borkh.) were grown on Murashige-Skoog (MS) nutrient medium supplemented with either sucrose or sorbitol or with sucrose and an elevated level of cytokinin. Shoot growth was recorded and concentrations of fructose, glucose, sorbitol, and sucrose were analyzed in nutrient media and shoots during a 6-week subculture period. Axillary branching was stimulated by high cytokinin and sorbitol media, with increased biomass production and carbohydrate use on the high BA-medium only.
Keywords: Pu; mikrolisäys; omena; Malus domestica; hiilihydraatit; sorbitoli; sytokiniinit; verso